Amazonian Medicine and the Psychedelic Revival: Considering the "Dieta" - David M. O'Shaughnessy; Ilana Berlowitz; Ilana Berlowitz (Frontiers Media S.A., 2021)
Background: In Peruvian Amazonian medicine, plant diets (dietas) are a fundamental and highly flexible technique with a variety of uses: from treating and preventing illness, to increasing strength and resilience, to rites of passage, to learning even medicine itself. Many of the plants used in diets are psychoactive; for example, one now well-known plant that can be dieted is Banisteriopsis caapi-the vine also used in the psychoactive brew ayahuasca. The use of ayahuasca has attracted increasing clinical attention towards Amazonian medicine in recent decades, and much work has focused on the potent DMT-containing ayahuasca brew, thus placing the tradition within the purview of psychedelic science.Aims: In comparison to ayahuasca, the properties of diets have been studied less often. Our work draws on data from Amazonian healers to examine plant diets as medical practices, while also considering their fit within the "set and setting framework" that is central to psychedelic research. We argue that the framework is not sufficiently broad for understanding diets, and thus the investigation aimed to expand the conceptual field of Amazonian medicine, particularly in the context of a renewed psychedelic science and its theoretical concepts.Design: We used qualitative data from interviews with Amazonian healers, applying a thematic analysis and contrasting findings with the available literature.Setting: Interviews were conducted in various locations in the San Martín province of Peru between 2015 and 2017.Participants: We selected and interviewed eight healers who had been extensively trained in traditional Amazonian medicine.Measures: Semi-structured interviews were used to gain insight into the healers' personal experiences with plant diets.Conclusions: Diets are complex but understudied medical practices that should not be explained by reference to pharmacology or psychology only. Intercultural and interdisciplinary research programmes are called for in order to not only better understand plant diets, but traditional Amazonian medicine on the whole.